A novel salt-tolerant bacterial consortium for biodegradation of saline and recalcitrant petrochemical wastewater. (15th April 2017) - Ahmadi, Mehdi; Jorfi, Sahand; Kujlu, Raheleh; Ghafari, Shokouh; Darvishi Cheshmeh Soltani, Reza; Jaafarzadeh Haghighifard, Nematollah
Abstract: Treatment of a saline petrochemical wastewater with BOD5 /COD ratio of less than 0.1 was investigated using a consortium consisted of three isolated salt-tolerant bacteria namely, Kocuria turfanesis, Halomonas alkaliphila and Pseudomonas balearica . Selected bacteria were isolated from petrochemical wastewater containing mineral salt mediums of 3% salinity. A lab-scale activated sludge bioreactor was used for startup in batch mode operation and after obtaining the MLSS concentration of about 3000 mg/L, the operation was changed to continuous flow mode to determine the biokinetic coefficients under different organic loading rates of 0.33–1.21 kg CODm −3 d −1 . The COD removal efficiency of 78.7%–61.5% was observed for treatment of real saline wastewater with a decreasing trend along with increasing the organic loading rate. In addition, results of kinetic investigation demonstrated that the yield(Y), endogenous decay coefficient (kd ), maximum reaction rate (Kmax ), maximum specific growth rate ( μ max ) and saturation constant ( K s ) were 0.54 mg VSS mg COD −1, 0.014 day −1, 1.23 day −1, 0.66 day −1, and 1315 mg L −1, respectively. Highlights: A saline and recalcitrant petrochemical wastewater was fully characterized and subjected to biological treatment. Three salt-tolerant bacteria including Kocuria turfanesis, Halomonas alkaliphila and Pseudomonas balearica were isolated. The biokinetic coefficients were studied under steady state conditions. COD Removal ranged between 61 and 78% for organic loading rates of 0.33–1.21 kg/COD/m 3 d.